THE PARADIGM DECONSTRUCTION OF THE DIVINE MORAL VALUE IN NOVEL RAHWANA PUTIH - Tri Astuti, Zuriyati, Ninuk Lustyantie (International Journal of Advanced Science and Technology, 2020)
The deconstruction of the divine moral value in Rahwana Putih’s novel by Sri Teddy Rusdy seeks to implement high-level Javanese teachings, Sastrajendra Hayuningrat Pangruwating Diyu. Rahwana figures are able to describe the high-level Javanese teachings as a form of deconstruction of the moral values ​​of God. This research is a qualitative descriptive study using deconstruction methods related to the moral values ​​of God in Rahwana Putih’s novel. The moral value of the Godhead which has been exploited all this time, that is, God, Man, has been deconstructed to become a Human God. Or in other words, humans become central or superior, whereas God becomes marginalized. The results of the deconstruction research on the moral values ​​of God have a place, namely a change of thought (1) sacred versus profane, (2) incarnation of god (Rama) good versus incarnation of evil god, (3) evil human versus good human, and good god versus evil god.